A Review of the Structural Fire Performance Testing Methods for Beam-to-Column Connections. (3rd November 2021) - Radzi, Noor Azim Mohd.; Hamid, Roszilah; Mutalib, Azrul A.; Amrul Kaish, A. B. M.
Abstract : The structural fire performance tests for beam-to-column connections are critical in determining their fire performance at high temperatures. The current standard fire testing methods provide the procedures for establishing the fire resistance of each construction element exposed to a standard fire. However, these methods cannot verify the fire behaviour of the connections between building elements. Researchers have performed numerous fire tests on beam-to-column connections despite the lack of structural fire performance testing methods. This paper presents a comprehensive literature review of the structural fire performance testing methods for beam-to-column connections. The major areas in this review are travelling fires, development of travelling fires on beam-to-column connections, fire testing considerations, fire testing criteria, recent fire testing, and loading applications. This paper identifies the key issues and challenges of the structural fire performance testing methods for beam-to-column connections. Finally, this paper provides recommendations and discusses the way forward for structural fire performance tests on beam-to-column connections.